The Song «Do Not Weep, Rachel» in the Stylistic Concept of the Sokyrynskyi (Halahanivskyi) Vertep - Kirsh, Ruslan (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2025)
Relevance of the study. The paraliturgical song “Do Not Weep, Rachel” is analyzed in the context of the Sokyryntsi (Halahan) Nativity Play, a unique monument of Ukrainian musical and theatrical culture of the 18th–19th centuries. The historical evolution of this work is traced from the medieval European mysteries Ordo Rachelis of the 11th century and the Ukrainian school drama to the Sokyryntsi Nativity Play where the motif of Rachel’s lament acquires a distinct stage form and symbolic depth. Purpose of the article. Specific attention is paid to the textological and musicological analysis which endows the piece with the theatricality and ensures its organic integration into the dramaturgy of the performance. Methodological basis. The melodic, rhythmic and intonational means of the song are examined on the basis of the Sokyryntsi Nativity Play manuscript of the mid-19th century, in comparison with 18th-century manuscript collections and printed Bohohlasnyks of the late 18th–19th centuries. This analysis elucidates the tragic emotionality of the piece and emphasizes its stage effectiveness. Results and conclusions. The unique dramaturgical solution of Rachel’s lament scene in the Sokyryntsi Nativity Play is outlined: the verses of the song are presented in a modified order that creates a special dramatic relief and alternates with the spoken lines of the characters, intensifying the emotional tension. It is shown that such a combination was chosen to strive the theatrical expressiveness and was also determined by the theological concept of the compilers of the Sokyryntsi Nativity Play. It has been established that within the structure of the Nativity Play the paraliturgical song “Do Not Weep, Rachel” is transformed into the dramatic center of the performance, functioning as a climactic peak, an emotional retardation, and a generalized moral-ethical evaluation of the events. It has been demonstrated that the combination of sacred song tradition with theater in the Sokyryntsi Nativity Play generates new artistic and semantic meanings, significant both for its own time and for the contemporary cultural discourse.